Level of Microplastic Contamination in the Ark Shell Arca senelis (Linnaeus 1785) from Baie Des Milliardaires (Île Boulay, Ébrié Lagoon System) - Konan, YAO Marcel; Yaya, BORA; Arthur, KONAN Kouadio Fabrice; Hicham, ABBAS Cheick (Geography, Earth Science and Environment: Research Highlights Vol. 10, 2025)
Aims: Area III of the Ébrié Lagoon system, located in the Abidjan district, is heavily polluted by plastics, which can impact its fauna, thereby posing serious health risks to humans. It is within this context that this study was conducted. This study aimed to assess the level of microplastic contamination in Arca senelis from Baie des milliardaires and their potential health risks for humans. Methodology: 120 samples of these bivalve mollusks were collected from this bay during January 2024. These samples were divided into three categories: category P, category M, and category G. The extraction of microplastics from the fresh tissue of these taxa was carried out by digestion in 10% KOH, followed by density separation after coagulation with a saturated ZnCl2 solution (1.6 g/cm³). The counting and characterization of microplastics were performed by stereomicroscopy, while the characterization of the constituent polymers was done by FT-IR. Results: All the individual of these different categories of bivalves had a mean of microplastics in their tissue greater than 2.7±2.4 microplastics/g of fresh weight. The sizes of microplastics were 90% less than 1000 µm. Furthermore, the observed MPs consisted of fragments, films, and fibers in almost equal proportions. Additionally, polyamides and polyacrylamides were the predominant polymers, representing 47.8% of the identified polymers. The estimated weekly and annual exposures to these microplastics was higher than that of developed countries. Conclusion: This study highlighted the significant contamination of these bivalves by microplastics, with significant health risks for humans.